Self-reported emotion regulation in children with autism spectrum disorder, without intellectual disability. (August 2020) - Burton, Talia; Ratcliffe, Belinda; Collison, James; Dossetor, David; Wong, Michelle
Highlights: Poorer self-reported emotion regulation skills were associated with decreased social skills and increased mental health difficulties. Social skills indicated to be a stronger predictor, compared to emotion regulation, of mental health difficulties. Findings support interventions which target both social skills and emotion regulation skills. Research conducted on community, school-based sample of children without intellectual disability. Abstract: Background: Emotion regulation (ER) may be a critical underlying factor contributing to mental health disorders in children with Autism Spectrum Disorder (ASD). Scant literature has utilised self-reported ER in children with ASD and explored the association between mental health and social skills. This study explored the association between self-reported ER skills, and parent/teacher proxy reports of ER, social skills, autism severity and mental health. Method: The pre-existing data set included a community sample of 217 students aged seven to 13-years ( M age = 9.51, SD = 1.26; 195 Male, 22 Female) with ASD. The study employed a correlational design, whereby existing variables were explored as they occurred naturally (Hills, 2011). Children self-rated ER, while parents and teachers rated ER, social skills, and mental health difficulties via standardised questionnaires. Results: Multiple regression analyses were conducted separately for parent and teacher reports. The linear combination of parent-reported emotion regulation, social skills, autism severity, and child-reported ER accounted for 46.5 % of the variance, compared to 58.7 % for the teacher-report analysis. Social skills appeared to be a stronger predictor of mental difficulties than emotional regulation irrespective of source. Conclusions: The current study suggests self-reported ER to be a significant contributor to mental health when in isolation. However, in the context of social skills and autism severity, ER is no longer a significant contributor in a child and adolescent community sample, in determining mental health. This suggests, that for children aged seven to 13-years with ASD, without ID, to reduce mental health difficulties, social skills may be the focus of intervention, with some focus on ER ability.